Penerapan Sistem Informasi Manajemen Puskesmas dengan Metode HOT-FIT di Puskesmas Wotu Kabupaten Luwu Timur - Feny Amelia, Feny; Ningsih, Nining Ade; Hasmah, Hasmah (Jurnal Kesmas Jambi, 2024)
The Puskesmas Management Information System (SIMPUS) is an advancement in health information technology that allows data and information to be available quicly, accurately, up-to-date, sustainable, and accountable. The HOT-FIT method has components that focus on the supporting environment and the system. The HOT-FIT model combines human, organisational, and technological elements. This research is descriptive qualitative, using data collection methods indepth interview. The informants consisted of 4 people, namely the main informant in charge of SIMPUS, supporting informants, namely the person in charge of the general clinic who uses SIMPUS and visiting patients, and the key informant, namely the head of the puskesmas. The research results of this indicate that from the information system and user statisfaction at Puskesmas Wotu East Luwu Regency, based on the human aspect is classified as good, while for the organisational aspect in the aspect of the organisational environment is still classified as not good, and the technology aspect for the quality of information is still classified as not good.Suggestions so that the implementation of SIMPUS at Puskesmas Wotu East Luwu Regency can run well, it is necessary to optimize implementation, and improve what is an obstacle in the human, organizational, and technological aspects. Keywords: Implementation of SIMPUS, HOT-FIT Method